Municipal Register of the City of Lawrence 1870, at 185 (1870) - (:unkn) unknown (My University, 1870)
Concerning Fires § 4: The city council may order that no gunpowder shall be kept within the city, except in tight casks or canisters; that not more than fifty pounds thereof shall be kept in any building within twenty-five rods of any other building, or if within ten rods, then not more than twenty-five pounds; nor more than one pound in any place, unless in copper, tin or brass canisters holding not more than five pounds each, and closely covered.
Keywords: GUNPOWDER - STORAGE